The Effectiveness of Indirect Correction Method Aided by Correction Codes - Kartika Stela; Julia Wulandari (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. This research discusses the effectiveness of indirect correction method supported by Karin Kleppin’s correction codes on writing assignments. The research participants were FIB UI’s German Studies Program students from the German Language IV course. This research aims to evaluate the effectiveness of this method in helping students recognize and correct morphological and syntactic errors. This is done by comparing the number of errors and analyzing them with the highest and lowest percentages of successful correction. Meanwhile, the effectiveness of this method in minimizing errors during the research was explored quantitatively by comparing the number of errors. The three corpora analysed in this research were the pretest, correction, and posttest writing assignments. The results indicate that punctuation, subjunctive mood, and grammatical case are the errors that had the highest percentages of successful correction, while errors modal verb, sentence structure, and missing elements had the lowest percentage of successful correction. 12 out of 15 errors analysed in this research were successfully recognized and corrected by at least 50% of all participants. Thus, this method can be said to be quite effective in recognizing and correcting errors. However, the effectiveness of this method in minimizing errors in the posttest did not bear significant results as only 16 out of 37 participants (43%) experienced a reduction in the number of errors.Keywords: indirect correction, correction code, writing assignment, morphological and syntactical errors, German as a foreign language